Optimization of Thermal Subsystem of Thermo Transducers for Measuring the Temperature of Gas Flows - Vasyl Fedynets; Ihor Vasylkivskyi (Energy Engineering and Control Systems)
The error of measuring the temperature of gas flows by contact methods consists of two main components: 1) the error that occurs in the process of measuring the physical quantity into which the temperature is converted (the error of the measuring means); 2) errors arising in the process of converting the temperature into a measured physical value using a thermo transducer. This component of the error is completely thermal in nature and is determined by the conditions of the thermal balance between the studied gas flow and the thermo transducer and has the greatest impact on the overall measurement error. It is determined by the combined action of the following factors: heat transfer due to radiation to or from the thermo transducer; heat removal from thermo transducer due to thermal conductivity; by converting part of the kinetic energy of the gas flow into thermal energy in the wall layer surrounding the thermo transducer; by convective transfer of heat from the wall layer to the sensitive element of the thermo transducer. Note also that if the temperature of the gas flow is non-stationary, then due to the thermo transducer's own heat capacity, it does not have time to register the time-varying temperature of the flow. Due to this, a dynamic component of the measurement error arises during the measurement of non-stationary temperatures. The article investigates the component error determined by the conditions of heat exchange between the gas flow and the thermo transducer.